2019
DOI: 10.22435/hsji.v12i2.2448
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents school students in Java and Sumatra are in greater risk of obesity

Abstract: Latar belakang: Indonesia masih menghadai beban ganda masalah gizi berkaitan dengan obesitas yang meningkat sementara masalah kurang gizi masih terjadi, termasuk pada remaja. Hasil penelitian masih terbatas, dalam hal aspek demografi dan geografi di Indonesia, sementara strategi pencegahan obesitas pada remaja membutuhkan intervensi yang lebih optimal. Tujuan: Studi ini bertujuan untuk memberikan gambaran masalah obesitas berdasarkan karakteristik populasi dan perilaku berisiko di region yang berbeda. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This study found that 32.9% of students had depressive symptoms, such as feeling sad or hopeless for two weeks, more than the 21.3% found in a 2007 study of Indonesian students by the global school-based student health survey (GSHS) (21). While the frequency of depressive symptoms in the form of suicide intents (5.4%) is nearly identical to the results of the 2015 GSHS study (5.14%), the prevalence of creating a suicide plan (6.2%) and attempting suicide (8.2%) is greater than the study results (5.54% and 2.39%) (22).…”
Section: Discussionsupporting
confidence: 66%
“…This study found that 32.9% of students had depressive symptoms, such as feeling sad or hopeless for two weeks, more than the 21.3% found in a 2007 study of Indonesian students by the global school-based student health survey (GSHS) (21). While the frequency of depressive symptoms in the form of suicide intents (5.4%) is nearly identical to the results of the 2015 GSHS study (5.14%), the prevalence of creating a suicide plan (6.2%) and attempting suicide (8.2%) is greater than the study results (5.54% and 2.39%) (22).…”
Section: Discussionsupporting
confidence: 66%
“…Smoking was among the top contributors to deaths and disability, particularly among men, as shown by the latest Indonesian Global Burden of Study 2017 [ 1 ]. The prevalence of smoking among men (15+ years) and boys (13–14 years) was among the highest in the world at 67% (2018) and 36% (2014), respectively [ 2 , 3 ]. Despite all this, the country is still not among the 181 signatories of the Framework Convention of Tobacco Control.…”
Section: Introductionmentioning
confidence: 99%
“…In the last 2 decades, the prevalence of smokers increased from 53.4% in 1995 to 66% in 2013. 1) In 2018, one in every two Indonesian adult males was a smoker (55.8%), while 1.9% of Indonesian females were smokers. 2) The increasing prevalence of smoking has also been observed in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…This survey was designed to include issues not covered in another national survey, the National Basic Health Research (Riset Kesehatan Dasar). 1) Understanding the profile of tobacco use among Indonesian adolescents has become an important investment, as it will support future programs by reducing the prevalence of smokers in Indonesia.…”
Section: Introductionmentioning
confidence: 99%